A clinicohematological profile of splenomegaly - Tangde, Ashwini; Sonwane, Bharat; Bindu, Rajan (International Journal of Research in Medical Sciences, 2019)
Background: Splenomegaly is a matter of considerable clinical concern as spleen is not normally palpable. Splenomegaly is associated with large number of disorders including hematological, infectious, congestive states related to portal hypertension, lymphohematogenous disorders, immunological conditions, storage disorders and miscellaneous conditions. So, all the cases of splenomegaly should be thoroughly investigated to ascertain etiology. Splenomegaly can be an important diagnostic clue to existence of an underlying pathology. The aim and objective of present study was to find out relative frequency of clinical conditions associated with splenomegaly, to study clinic-hematological profile of splenomegaly and to find out the role of hematological investigations as a diagnostic tool in elucidating etiopathogenesis of splenomegaly. Methods: This was a cross sectional, observational study. Study was conducted on 135 pediatric as well as adult patients with splenomegaly admitted in medical ward, Government Medical College and tertiary care hospital Aurangabad, Maharashtra, India from December 2015 to October 2017. Hematological parameters of 135 cases of splenomegaly were analysed and correlated with clinical findings. Results: Study comprises 135 patients. Age range was 3 months to 78 years. Males (54.81%) were affected more commonly than females (45.19%). The most common presenting complaint was fever (59.26%) followed by generalized weakness (51.11%) and pallor (44.44%). Majority of cases (48.15%) had grade II splenomegaly. Splenomegaly was associated with hepatomegaly (60.74%) and lymphadenopathy (18.52%). The commonest cause of splenomegaly found was anemia (39.26%) followed by hematological malignancies (20.74%), congestive states (11.85%) and infections (11.85%). Hematological investigations revealed diagnosis in majority of cases (71%). Conclusions: Splenomegaly is an important clinical sign that must be investigated thoroughly as most of the common causes are treatable. Hematological causes outnumbered the non-hematological causes of splenomegaly. Hematological profile in cases of enlarged spleen are of utmost importance as a diagnostic or additional tool in elucidating the etiogenesis of splenomegaly.